Determination of the effects of bone marrow derived mesenchymal stem cells and ovarian stromal stem cells on follicular maturation in cyclophosphamide induced ovarian failure in rats - Huseyin Erdinc Besikcioglu; Gulistan Sanem Sarıbas; Candan Ozogul; Meral Tiryaki; Sevtap Kilic; Ferda Alpaslan Pınarlı; Ozlem Gulbahar (Elsevier, 2019)
Objective: Chemotherapy causes depletion of primordial follicles that leads to premature ovarian failure in female cancer survivals. We investigated the effect of bone marrow derived mesenchymal (BMMSCs) and ovarian stromal stem cells (OSSCs) on follicle maturation in chemotherapy induced ovarian failure. Material and methods: Thirty six Wistar Albino female rats were divided into three groups. Cyclophosphamide at a dose of 200 mg/kg was intraperitoneally (IP) given to the rats in all groups two times. 4 × 106 BMMSCs (IP) was injected to the group-2 and 4 × 106 OSSCs (IP) was injected to the group-3. Serum Anti-Müllerian Hormone (AMH) levels was determined with ELISA and primordial follicles were counted for investigation of primordial follicle reserve. The ovarian structure were evaluated histomorphologically. Localization of BrdU labeled stem cells, the expression of the cell cycle regulator p34Cdc2, gap junction protein p-connexin43 and intraovarian regulators of folliculogenesis Bone Morphogenic Protein 6 and 15 (BMP-6 and BMP-15) were investigated by immunohistochemistry. Results: The immunstaining of BMP-6 was higher in oocytes of group-3 more than group-1 and group-2. The immunpositivity of p34cdc2 and BMP-15 were also higher in follicular cells of group-3 than the other groups. The presence of p-connexin43 in group-3 was determined more than group-1 and group-2. The ovarian follicles with normal histological structure were observed just in group-3. Although, The AMH levels were decreased in rats from all groups at the end of experimental procedure the primordial follicle counts in group-3 was significantly higher than group-1. Conclusion: Our findings suggest that OSSCs have more protective effect on follicle maturation than BMMSCs in cyclophosphamide induced ovarian damage. Keywords: Cyclophosphamide, Ovary, Ovarian follicle, Stem cells